Analysis on The Effect of Bio-addictive Mixtures Eugenol in Pertamax Green 95 Fuel on Engine Performance - Nursiam, Kuat; Sonika Maulana; Sumbodo, Wirawan; Naryanto, Rizqi Fitri; Fitriyana, Deni Fajar (Universitas Negeri Semarang, 2025)
Improving energy efficiency and reducing exhaust emissions from motor vehicles have become a primary focus in the transition towards green energy in the transportation sector. This study aims to analyze the effect of adding eugenol, the main compound in clove oil, to Pertamax Green fuel on engine performance, fuel consumption efficiency, and exhaust emissions in a 2018 Honda Vario 125 motorcycle. The research method is an experimental approach with variations in the fuel mixture of pure Pertamax Green (P0), Pertamax Green + 0.2% eugenol (P1), 0.5% eugenol (P2), and 1% eugenol (P3). Testing was conducted using a dynamometer to measure torque and power, a static method for fuel consumption, and a gas analyzer to analyze CO and HC emission levels. The results showed that adding eugenol generally improved engine torque and power. The P2 mixture (0.5% eugenol) produced the highest torque of 8.48 N.m at 5000 rpm and maximum power of 7.2 HP at 8000 rpm, an increase of 38% and 18%, respectively, compared to pure Pertamax Green. Fuel consumption efficiency also increased by 4.1% with the P2 mixture, while excessive eugenol (1%) decreased efficiency due to slower combustion. In terms of emissions, CO levels decreased by up to 16.7%, and HC levels reduced by up to 22.54% as the concentration of eugenol increased.